Impact of sarcopenia on biliary drainage during neoadjuvant therapy for pancreatic cancer - Kunio Kataoka; Eizaburo Ohno; Takuya Ishikawa; Kentaro Yamao; Yasuyuki Mizutani; Tadashi Iida; Hideki Takami; Osamu Maeda; Junpei Yamaguchi; Yukihiro Yokoyama; Tomoki Ebata; Yasuhiro Kodera; et al. (Korean Society of Gastrointestinal Endoscopy, 2024)
Background/Aims Since the usefulness of neoadjuvant chemo(radiation) therapy (NAT) for pancreatic cancer has been demonstrated, recurrent biliary obstruction (RBO) in patients with pancreatic cancer with a fully covered self-expandable metal stent (FCSEMS) during NAT is expected to increase. This study investigated the impact of sarcopenia on RBO in this setting. Methods Patients were divided into normal and low skeletal muscle index (SMI) groups and retrospectively analyzed. Patient characteristics, overall survival, time to RBO (TRBO), stent-related adverse events, and postoperative complications were compared between the two groups. A Cox proportional hazard model was used to identify the risk factors for short TRBO. Results A few significant differences were observed in patient characteristics, overall survival, stent-related adverse events, and postoperative complications between 38 patients in the normal SMI group and 17 in the low SMI group. The median TRBO was not reached in the normal SMI group and was 112 days in the low SMI group (p=0.004). In multivariate analysis, low SMI was the only risk factor for short TRBO, with a hazard ratio of 5.707 (95% confidence interval, 1.148-28.381; p=0.033). Conclusions Sarcopenia was identified as an independent risk factor for RBO in patients with pancreatic cancer with FCSEMS during NAT.